Mapping Center-Pivot, Irrigation Systems in Sudan, Using Remote Sensing and GIS Techniques - Kheiralla, Abdalobalab; Eltaib Ganawa; Omar A. Allteyb; Salahalden A. Ahmed; Mohamed M. Mohamed (University of Khartoum Engineering Journal, 2025)
Center-pivot irrigation systems have been the cornerstone of current growing agricultural sector in Sudan for animal feed and food production. This paper presents the mapping center-pivot irrigation systems in Sudan using remote sensing and GIS techniques for national and regional agricultural auditing, managing of water and energy use and other policy implications. The data related to the locations of the pivots was collected employing remote sensing images of Landsat 8 satellite, with a spatial resolution of 15 meters. A total of 1373 active pivots and 168,320 Fed. covered area were recorded in Sudan, 2020, mostly in the River Nile (774), Northern (269), Khartoum (248), and Kurdufan (49) states. The research also included information on a commercial agricultural project in Khartoum state that is irrigated by center pivot irrigation systems since 2009. Pivots identification showed increase in numbers from 29 to 105 for years 2009 to 2020, respectively. Various map layers such as irrigation network, soil types and cultivated crops were prepared using remotely sensing data along with the existing data. The irrigation network map layer consisted of pumps station at Blue Nile River and main canal distributed to sub-canals and secondary canals to irrigate 14,112 Fed. The soil map layer is qualitatively classified into loam and sandy clay loam soils, while the cultivated crops showed Rhodes, Alfalfa, and Corn covered 79, 20 and 6 pivots, respectively. This study provides sample evidence that remote sensing and GIS techniques could be used to map center-pivot irrigation systems to enhance agricultural production management